NILAI AKHLAK DALAM NOVEL SURAT UNTUK MUSLIMAH KARYA AYESHA ELHIMAH - Erlina Zahar; Sri Wahyuni (Universitas Batanghari, 2021)
This study aims to describe the religious values associated with the human relationship with Allah (Hablumminallah), which includes aspects of repentance, aspects of patience, aspects of gratitude, aspects of tawakal, aspects of sincerity, aspects of raja’ in the novel Surat Untuk Muslimah by Ayesha El Himah. This research is a descriptive qualitative type. Qualitative descriptive research is a research that describes an event with words or a description of the condition of the subject in a certain environment and situation. The results of this study illustrate that the religious value of the human relationship with God (Hablumminallah) includes; aspects of repentance, aspects of patience, aspects of gratitude, aspects of tawakal, aspects of sincerity, aspects of raja’ in the novel Surat Untuk Muslimah by Ayesha El Himah. (1) there are five expressions of aspect of repentance, (2) there are 24 expressions of aspect of patience, (3) there are 14 expressions of aspect of gratitude, (4) there are 16 expressions of aspect of tawakal, (5) there are 21 expressions of sincere aspect, (6) there are 31 expressions of aspect of raja’. The most dominant aspect of religious values related to human relations with Allah (Hablumminallah) in Ayesha El Himah's Novel Surat Untuk Muslimah is the aspect of raja’ which occurred 31 times. Meanwhile, the least is a repentant aspect which occurred five times. Thus, it can be concluded that the novel Surat Untuk Muslimah by Ayesha El Himah contains many religious values related to human relations with God (Hablumminallah) because this novel tells a lot about the human faith